IMPLIKASI PERNIKAHAN USIA DINI TERHADAP KELANGSUNGAN KEHIDUPAN RUMAH TANGGA DI KABUPATEN OGAN KOMERING ILIR (PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM) - Rian Purnama Suci (SOL JUSTICIA, 2021)
Provisions regarding the minimum age limit for carrying out marriage are contained in Article 7 paragraph (1) of Law Number 1 of 1974 as amended by Law of the Republic of Indonesia Number 16 of 2019 which states that "Marriage is only permitted if the man and woman have reach the age of 19 years. On the other hand, Islamic law does not specify a certain age limit for people to carry out marriages. Law Number 1 of 1974 still provides for the possibility of deviating from the age requirement for marriage. This is regulated in Article 7 paragraph (2) of Law Number 1 of 1974 as amended by Law of the Republic of Indonesia Number 16 of 2019, namely with a dispensation from the Court for those who have not reached the minimum age limit. the effect of early marriage on the divorce rate and the efforts that can be made to minimize early marriage. This research is a normative research. The legal materials studied include primary materials consisting of statutory regulations, and secondary legal materials sourced from legal books (text books), legal journals, papers or views of legal experts contained in the mass media, dictionaries and encyclopedias. , and the internet. The results of this study indicate that early marriage has relevance to the high rate of divorce (lawful divorce and talak divorce). Child marriage has an impact on the household life of each couple. Among other things, the emergence of marital disputes caused by various factors, lack of maturity in thinking and the ability to determine attitudes and actions in dealing with any problems that arise so that not a few end up in separation and divorce.